Rutter's Child and Adolescent Psychiatry 2008
DOI: 10.1002/9781444300895.ch46
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders

Abstract: In the evaluation of any treatment, it is extremely important to gather information about the longlasting effects of treatment by collecting follow-up data. Follow-up research aims to measure effects of treatment over time to determine if the treatment has resulted in a structural improvement or if clients relapsed to pre-assessment levels. The importance of follow-up data for the evaluation of neurofeedback has been noted repeatedly. Heinrich, Gevensleben, and Strehl (2007), for example, suggest investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
2
19
0
1
Order By: Relevance
“…Third, the overall identification rates for mild and severe intellectual disability and for ASD are consistent with the results of previous research 1–3 5 6 16 17 19. Finally, variation in the identification rates are largely consistent with the results of previous research in indicating strong associations between SEP and less severe intellectual disabilities and between male gender and ASD 1–3 5 6 16 17 19. The cross-sectional nature of the design obviously imposes severe limitations on the identification of any causal pathways that may underlie the observed associations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Third, the overall identification rates for mild and severe intellectual disability and for ASD are consistent with the results of previous research 1–3 5 6 16 17 19. Finally, variation in the identification rates are largely consistent with the results of previous research in indicating strong associations between SEP and less severe intellectual disabilities and between male gender and ASD 1–3 5 6 16 17 19. The cross-sectional nature of the design obviously imposes severe limitations on the identification of any causal pathways that may underlie the observed associations.…”
Section: Discussionsupporting
confidence: 88%
“…The estimated prevalence of I/DD is approximately 3–4% for children in high income countries,1–3 although much higher rates have been reported in some studies 4. Intellectual and developmental disabilities are associated with increased mortality and morbidity, increased risk of social exclusion, and significant demands on families and health and social care agencies 5 6. The lifetime costs to health and social care agencies of an individual with autism has been estimated at £2.4 million 7…”
Section: Introductionmentioning
confidence: 99%
“…Second, a number of high quality reviews of this area have been published over the past decade. [14][15][16][17][18][19][20] Instead, we reviewed these reviews and supplemented them with a review of epidemiological studies published since 2000. These additional studies were identified by a combination of: (1) literature searches undertaken in September 2010 using the databases Medline and PsycINFO; (2) consultation with recognised experts in the field.…”
Section: The Prevalence Of Learning Disabilities Among Children With mentioning
confidence: 99%
“…Given this, we do have some limited understanding of the biological associations with ASD and other co-morbidities. As mentioned in Chapter One, it is estimated that more than half of children with ASD have an ID (Baird, et al, 2006;van Engeland and Buitelaar, 2008). There is evidence that people with lower cognitive abilities and people have poorer health than their peers (Krahn, et al, 2006).…”
Section: Biologymentioning
confidence: 99%
“…Also, dietary challenges are seen in adults and children with ASD. Evidence suggests there is a link between ASD and compromised immune systems, such as gluten allergies, and other medical causes (van Engeland and Buitelaar, 2008;Pessah, et al, 2008). Restricted diet is a common issue for many people with ASD, due to sensory preferences, and often leads to poor nutrition and weight concerns (Heller, et al, 2013).…”
Section: Biologymentioning
confidence: 99%